The Naik Dango Tradition In The Agricultural Practices Of The Dayak Kanayatn Community, West Kalimantan: A Maqasid Al-Shariah Perspective Of Abd Al-Majid Al-Najjar - Agung Prakoso, Imam; Mukharrom, Tamyiz; Yusdani (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This Research examines the Naik Dango tradition practiced by the Dayak Kanayatn community in West Kalimantan from the perspective of Maqasid Syariah Abd al-Majid al-Najjar. This tradition is not only a ritual of gratitude for the harvest, but also a social, ecological, and economic system that supports community food security. The method used is a descriptive qualitative approach with ethnographic techniques through participatory observation, interviews, and documentation. The results of the study indicate that Naik Dango contains values of protection for life (ḥifẓ al-nafs), property (ḥifẓ al-māl), society (ḥifẓ al-mujtama‘), and the environment (ḥifẓ al-muḥīṭ al-māddī), as examined within the framework of maqasid syariah. This tradition supports the preservation of local seeds, solidarity-based food distribution, and intergenerational agrarian education. The conclusion of the study confirms that Naik Dango is a local manifestation of universal Islamic values in maintaining welfare and can be used as an alternative model in formulating sustainable food security strategies based on local wisdom